Is female orgasm an earth-moving experience: an Egyptian experience. Issue 3 (September 2015) - Younis, Ihab; El-Esawy, Fatma; Abdel-Mohsen, Riham
Abstract : Background: Orgasm problems in women are the second most frequently reported female sexual dysfunctions. The mechanisms triggering female orgasm are still unclear. Many non-physical factors, as culture and religion, can affect the incidence and characters of orgasm. The current study was conducted with the purpose of obtaining some information about orgasm in a sample of Egyptian women to fill the gap in this respect. Patients and Methods: A self-report questionnaire was used in this study that included 164 women attending the outpatient clinic of Benha University Hospital. All participants were sexually active and their ages range was 20 to 60 years. Anonymity of participants was secured. Results: The time needed to reach orgasm was >5 min but <10 min in 42.2% of participants. When they fail to obtain an orgasm, 32.9% of women fake it. Adescription of orgasm as a combination of shuddering all over the body and a nice feeling localized to the genitals was given by 42.2% of women. Female ejaculation was experienced by 40.2% of the participants and half of them were multiorgasmic. Most women (54.9%) consider not reaching orgasm is not a failure. The usual method of reaching was penile thrusting for 51.2%, while 48.8% could reach orgasm via manual stimulation only. Conclusion: Most women can reach orgasm in more than 50% of sexual encounters even if they were exposed to FGC. Women fake orgasm to accelerate finishing ofintercourse. Coital position has an effect on ability to attain an orgasm. Advance in age causes a decrease in both frequency and time needed to reach orgasm.